Folk dolls as a universal object in psychotherapeutic work with women - Bochkarjova, Іolanta; Zaichikova, Т.; Бочкарьова, Іоланта; Зайчикова, Т. (Київський національний університет імені Тараса Шевченка, 2017)
The article is devoted to the analysis of the potential of Slavic rag doll in modern psychotherapeutic practice (Doll-therapy, the method of Art- therapy). It examines the phenomenon of ethnic dolls as psychotherapeutic object, as well as shows the versatility of slavic dolls in therapeutic practice of psychodynamic approach, Jung's analysis, transactional analysis and Gestalt-therapy. A folk doll represents a unique tool in psychotherapeutic work with women.

Стаття присвячена аналізу потенціалу слов'янської вузлової ляльки в сучасному психотерапевтичному середовищі (лялькотерапія, метод арт-терапії). Розглядається феномен етнічної ляльки як психотерапевтичного об'єкта. Показана універсальність слов'янської ляльки в терапевтичній практиці психодинамічного підходу, юнгіанського аналізу, трансактного аналізу і гештальт-терапії. Народна лялька представлена як унікальний засіб в психотерапевтичній роботі з жінками.
Народна лялька як універсальний об'єкт у психотерапевтичній роботі з жінкою
Keywords: народна лялька; лялькотерапія; універсальний символ; жінка; психотерапевтичний об'єкт; folk doll; Doll-therapy; a universal symbol; woman; psychotherapeutic object